Evaluation of the Antibacterial Activity and Cell Response for 3D-Printed Polycaprolactone/Nanohydroxyapatite Scaffold with Zinc Oxide Coating - Cho, Yong Sang (Polymers (Basel), 2020)
Among 3D-printed composite scaffolds for bone tissue engineering, researchers have been attracted to the use of zinc ions to improve the scaffold’s anti-bacterial activity and prevent surgical site infection. In this study, we assumed that the concentration of zinc ions released from the scaffold will be correlated with the thickness of the zinc oxide coating on 3D-printed scaffolds. We investigated the adequate thickness of zinc oxide coating by comparing different scaffolds’ characteristics, antibacterial activity, and in vitro cell response. The scaffolds’ compressive modulus decreased as the zinc oxide coating thickness increased (10, 100 and 200 nm). However, the compressive modulus of scaffolds in this study were superior to those of other reported scaffolds because our scaffolds had a kagome structure and were made of composite material. In regard to the antibacterial activity and in vitro cell response, the in vitro cell proliferation on scaffolds with a zinc oxide coating was higher than that of the control scaffold. Moreover, the antibacterial activity of scaffolds with 100 or 200 nm-thick zinc oxide coating on Escherichia coli was superior to that of other scaffolds. Therefore, we concluded that the scaffold with a 100 nm-thick zinc oxide coating was the most appropriate scaffold to use as a bone-regenerating scaffold, given its mechanical property, its antibacterial activity, and its in vitro cell proliferation.